Analisis K-Means Clustering untuk Klasterisasi TPT Kabupaten/Kota di Jawa Barat 2021–2023 - 10060121055, Ainani Tajriyan Muntaharridwan (Bandung Conference Series: Statistics, 2025)
Abstract. The Open Unemployment Rate (TPT) is a crucial indicator reflecting the labor market and economic conditions of a region. West Java Province has consistently recorded relatively high TPT figures over the past three years, despite showing a downward trend. This study aims to cluster districts/cities in West Java based on their TPT data from 2021 to 2023 using the K-Means Clustering algorithm. The data used is secondary data obtained from the Central Statistics Agency (BPS). The analytical process includes assumption testing, data normalization using Z-Score, and determining the optimal number of clusters through the Silhouette Coefficient method. The results show that two optimal clusters were formed: the first cluster consists of five regions with relatively low TPT, while the second cluster includes twenty-two regions with relatively high TPT. The clustering visualization demonstrates a clear separation between clusters, and silhouette values above 0.5 indicate strong clustering performance. This research provides a data-driven basis for local governments to formulate more targeted and effective employment policies. It also contributes to future studies in applying data mining techniques to social and economic issues. Abstrak. Tingkat Pengangguran Terbuka (TPT) merupakan indikator penting yang mencerminkan kondisi ketenagakerjaan dan perekonomian suatu wilayah. Provinsi Jawa Barat tercatat memiliki angka TPT yang cukup tinggi dalam tiga tahun terakhir, meskipun menunjukkan tren penurunan. Penelitian ini bertujuan untuk mengelompokkan kabupaten/kota di Provinsi Jawa Barat berdasarkan kesamaan tingkat pengangguran terbuka pada tahun 2021 hingga 2023 menggunakan algoritma K-Means Clustering. Data yang digunakan merupakan data sekunder dari Badan Pusat Statistik (BPS). Proses analisis diawali dengan uji asumsi, normalisasi data menggunakan Z-Score, serta validasi jumlah cluster optimal menggunakan metode Silhouette Coefficient. Hasil penelitian menunjukkan bahwa dua cluster optimal terbentuk: cluster pertama terdiri dari lima kabupaten/kota dengan TPT relatif rendah, sedangkan cluster kedua terdiri dari dua puluh dua wilayah dengan TPT relatif tinggi. Visualisasi hasil clustering menunjukkan pemisahan yang jelas antar cluster, dan validasi dengan nilai silhouette rata-rata > 0,5 menunjukkan kualitas pengelompokan yang baik. Penelitian ini diharapkan menjadi dasar rekomendasi bagi pemerintah daerah dalam merancang kebijakan ketenagakerjaan yang lebih terarah dan efisien, serta sebagai referensi dalam pengembangan penelitian lanjutan menggunakan metode data mining dalam bidang sosial ekonomi.